Efforts to overcome hypoxia condition in Balb/c mouse macrophages after intraperitoneal SRBC immunization - Pungguri Ayu Nega Sarsanti (Medical Journal of Indonesia, 2019)
BACKGROUND Activated macrophages require increased oxygen to destroy foreign bodies, leading to an increase in the levels of reactive oxygen species (ROS). Therefore, macrophages would experience hypoxic and oxidative stress conditions at the same time. Thus, this study was aimed to evaluate the mechanism of the activated macrophages to overcoming this dual condition.